“I Don’t Know if I Can Handle It All”: Students’ Affect During Remote Education in the COVID-19 Pandemic in Brazil - Comelli, Felipe Augusto de Mesquita; da Costa, Michel; dos Santos Tavares, Elisabeth (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2021)
The COVID-19 pandemic has impacted society in different areas. In education, several reports show the deleterious effects of the disease on the physical and mental health of students, family members, and teachers around the world. Also, in Brazil, affect studies indicate the prevalence of anxiety, stress, and depression among students. The present research, of a qualitative nature, explores what it means, under the lens of affect and from the student’s perspective, to experience remote education during the COVID-19 pandemic. An online questionnaire of 41 closed- and open-ended questions was given to 363 students from a public school in southeastern Brazil. This article analyzes the affective fields that emerged from the discursive textual analysis of the students’ responses (n = 100). Four affective fields were categorized: friends, classes, home, and teachers; intersecting emotions, attitudes, values, beliefs, and motivation. In general, students expressed more negative than positive affect but a positive disposition toward face-to-face classes. Boys focused their affect more on classes, while girls on teachers. The affective fields allow us to consider the friends–home–teachers tripod as fundamental to overcoming the phenomenon of affective fatigue that has been identified.